2016
DOI: 10.1167/iovs.15-18689
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Biomechanical Response Following Collagen Cross-Linking With Rose Bengal–Green Light and Riboflavin-UVA

Abstract: The deformation of UVX-treated corneas was smaller than the RGX-treated corneas. However, the reconstructed corneal mechanical parameters reveal that RGX produced in fact larger stiffening of the treated region (100-μm depth) than UVX (137-μm depth). Rose bengal-green light stiffens the cornea effectively, with shorter treatment times and shallower treated areas. Dynamic air puff deformation imaging coupled with mechanical simulations is a useful tool to characterize corneal biomechanical properties, assess di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…RF-CXL is toxic to stromal cells and corneal nerves although an in vivo confocal microscopy study confirmed that both the cell density and the nerve density returned to baseline levels after 1 year (92). In animal models, RF-CXL increased corneal stiffness as determined by air puff corneal deformation imaging with finite element modeling and by optical coherence elastography (93,94), consistent with previous studies in ex vivo-treated corneas that indicated~2-fold increase in Young's modulus (95)(96)(97)(98)(99). Responses to RF-CXL in rabbit corneas included downregulation of genes for ECM components and upregulation of glycan and proteoglycan glycosylation (100) as well as stromal cell death throughout the anterior and middle stroma (65).…”
Section: Biomechanical Stiffeningsupporting
confidence: 86%
“…RF-CXL is toxic to stromal cells and corneal nerves although an in vivo confocal microscopy study confirmed that both the cell density and the nerve density returned to baseline levels after 1 year (92). In animal models, RF-CXL increased corneal stiffness as determined by air puff corneal deformation imaging with finite element modeling and by optical coherence elastography (93,94), consistent with previous studies in ex vivo-treated corneas that indicated~2-fold increase in Young's modulus (95)(96)(97)(98)(99). Responses to RF-CXL in rabbit corneas included downregulation of genes for ECM components and upregulation of glycan and proteoglycan glycosylation (100) as well as stromal cell death throughout the anterior and middle stroma (65).…”
Section: Biomechanical Stiffeningsupporting
confidence: 86%
“…The average time to highest concavity (HC) was 16.2 ms (± 0.24), while 18.38 ms has been reported for human corneas [35] and 17 ms in rabbits [8]. The shape of the temporal profiles is also different, being very symmetrical and steeper than real corneas in MCs (Fig 9 right), following closely the air puff pressure profile over time.…”
Section: Discussionmentioning
confidence: 68%
“…In refractive surgery, where corneal thickness is reduced as a result of corneal reshaping to eliminate refractive errors, pre-operative measurements of corneal biomechanics could help identifying patients at risk of iatrogenic ectasia [6]. Individual knowledge of the cornea can help in customizing certain treatments for keratoconus such as intracorneal ring segment implants [7] or to monitor the effectiveness of corneal collagen cross-linking [8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Alternative treatments now aim to avoid UV light exposure to the eye. These include Rose Bengal green light crosslinking 8 and core protein decorin crosslinking that does not require any light exposure. 9 Collagen-based biomaterials also frequently require structural reinforcement through chemical crosslinking.…”
mentioning
confidence: 99%